Computer-Assisted Qualitative Data Analysis Software, Phenomenology, and Colaizzi's Method. (December 2022) - Vignato, Julie; Inman, Michaela; Patsais, Micayla; Conley, Virginia
Technology is widely used to support qualitative research. Computer-Assisted Qualitative Data Analysis Software (CAQDAS) encompasses complementary technologies to support qualitative analysis. Advantages of CAQDAS include efficient management of data and transparency in analysis. Disadvantages include heavy emphasis on coding as a distractor from analysis and considerable time to learn the program. In this methods article, we, as less experienced, qualitative researchers describe our experiences using NVivo, a CAQDAS program, in a descriptive phenomenological study using Colaizzi's method. Over 1 year, 24 postpartum women were given a secure research link to record their experiences with pain and depression during the third trimester of pregnancy. Although NVivo analysis was helpful, the philosophy of phenomenology, reflexivity, and Colaizzi's method directed researchers away from NVivo for the final summation. Recommendations for future use of CAQDAS used concurrently with Colaizzi's method include the use of word clouds and other visualizations for bracketing and triangulation.